2008
DOI: 10.1371/journal.ppat.0040036
|View full text |Cite
|
Sign up to set email alerts
|

Forward Genetic Analysis of the Apicomplexan Cell Division Cycle in Toxoplasma gondii

Abstract: Apicomplexa are obligate intracellular pathogens that have fine-tuned their proliferative strategies to match a large variety of host cells. A critical aspect of this adaptation is a flexible cell cycle that remains poorly understood at the mechanistic level. Here we describe a forward genetic dissection of the apicomplexan cell cycle using the Toxoplasma model. By high-throughput screening, we have isolated 165 temperature sensitive parasite growth mutants. Phenotypic analysis of these mutants suggests regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
169
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(180 citation statements)
references
References 69 publications
10
169
1
Order By: Relevance
“…To obtain a complemented cell line, we used the ToxoDB genomic database to look for a cosmid clone from the ToxoSuperCos library 39 that would be overlapping the TgAtg4 locus and we found clone ToxPG30. Clone I9 tachyzoites were transfected with 100 µg of the ToxPG30 cosmid.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain a complemented cell line, we used the ToxoDB genomic database to look for a cosmid clone from the ToxoSuperCos library 39 that would be overlapping the TgAtg4 locus and we found clone ToxPG30. Clone I9 tachyzoites were transfected with 100 µg of the ToxPG30 cosmid.…”
Section: Methodsmentioning
confidence: 99%
“…In Plasmodium falciparum, the causative agent of malaria, four Neks were identified, two of which (PfNek2 and PfNek4) are essential for sexual development in the mosquito vector, whereas PfNek1 is required for progression through the erythrocyte cycle (Reininger et al, 2005;Reininger et al, 2009;Xue et al, 2011). Seven Neks were identified in the Toxoplasma genome (Peixoto et al, 2010), but have not been experimentally addressed except one: TgNek1 has been genetically connected to lytic cycle progression as a temperature-sensitive (ts) mutant named V-A15 was identified in a chemical mutagenesis screen for lytic cycle progression (Gubbels et al, 2008a). In this preliminary analysis, mutant V-A15 displayed uncoupling of cytokinetic progression from mitotic progression.…”
Section: Introductionmentioning
confidence: 99%
“…However, in case the GOI is essential during the asexual life cycle, the generation of mutant parasites is impossible. In order to characterise essential factors in detail, three strategies are currently being employed with great success: (i) generation of temperature sensitive mutants followed by complementation cloning to identify the mutated gene (Gubbels et al 2008); (ii) employment of a tetracycline inducible (Tet-inducible) transactivator system (Meissner et al 2002) and (iii) a recently established degradation system (ddFKBP-system) that allows the rapid regulation of a protein of interest (Herm-Gotz et al 2007). However, as mentioned above, the absence of a "real" high throughput system, such as siRNA based methods (Ullu et al 2004), is seriously hampering a genome wide approach as performed in other eukaryotes.…”
Section: Molecular Tools For Identification and Characterisation Of Ementioning
confidence: 99%
“…Although the generation of temperature sensitive mutants appears to be relatively straight forward, the isolation of the respective locus might be complicated in case several genes have been mutated or the respective mutation has a dominant effect. However, with the optimisation of complementation technologies (Striepen et al 2002, Gubbels et al 2008, this technique has been currently demonstrated to be very powerful for the identification and isolation of novel essential genes (Gubbels et al 2008). The obvious advantage of this strategy is that hypothetical genes that might otherwise be neglected in targeted approaches will be identified with equal probability.…”
Section: Molecular Tools For Identification and Characterisation Of Ementioning
confidence: 99%
See 1 more Smart Citation